Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0092240
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Clinical Manifestations in Asymptomatic Dengue Infection Is Attributed to Broad Down-Regulation and Selective Up-Regulation of Host Defence Response Genes

Abstract: ObjectivesDengue represents one of the most serious life-threatening vector-borne infectious diseases that afflicts approximately 50 million people across the globe annually. Whilst symptomatic infections are frequently reported, asymptomatic dengue remains largely unnoticed. Therefore, we sought to investigate the immune correlates conferring protection to individuals that remain clinically asymptomatic.MethodsWe determined the levels of neutralizing antibodies (nAbs) and gene expression profiles of host immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 74 publications
0
23
0
3
Order By: Relevance
“…However, we cannot delineate which of the observed phenomena can be attributed to antigen specific responses. Therefore, future studies using tools to identify DENV-specific T cells and B cells in strictly asymptomatic individuals will be of great value (38,53) One previous report analyzing differential gene expression in asymptomatic DENV-infected individuals investigated patients in the convalescent phase of the disease, as demonstrated by the absence of detectable viral loads (57). Unsurprisingly, they found that most genes related to host defense mechanisms were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot delineate which of the observed phenomena can be attributed to antigen specific responses. Therefore, future studies using tools to identify DENV-specific T cells and B cells in strictly asymptomatic individuals will be of great value (38,53) One previous report analyzing differential gene expression in asymptomatic DENV-infected individuals investigated patients in the convalescent phase of the disease, as demonstrated by the absence of detectable viral loads (57). Unsurprisingly, they found that most genes related to host defense mechanisms were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of rotavirus gastroenteritis have found that serum TNF-a is associated significantly with diarrhoea incidence when compared to healthy controls and controls with non-viral diarrhoea [19,20]. Other viral infections, including hepatitis B and dengue virus, induce different proinflammatory cytokine gene expression in symptomatic compared to asymptomatic individuals [21,22]. In the case of dengue, symptomatic individuals had higher expression of many proinflammatory cytokine genes compared to asymptomatic individuals, suggesting that some of dengue's most severe outcomes may be caused partially by an inflammatory response [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other viral infections, including hepatitis B and dengue virus, induce different proinflammatory cytokine gene expression in symptomatic compared to asymptomatic individuals [21,22]. In the case of dengue, symptomatic individuals had higher expression of many proinflammatory cytokine genes compared to asymptomatic individuals, suggesting that some of dengue's most severe outcomes may be caused partially by an inflammatory response [22]. Indeed, cytokines are thought to cause diarrhoea in other infections without primary gastrointestinal tropism (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The healthy controls were the household member of each dengue patient and there was significant increase in IL-4 levels in dengue patients. This study was done by Yeo et al 19 involving 29 pairs in the study.…”
Section: Why Il-4 Was Analysed?mentioning
confidence: 99%